The Female FTSE Board Report 2015: Putting the UK Progress into a Global Perspective - Vinnicombe, Susan; Doldor, Elena; Sealy, Ruth; Pryce, Patricia; Turner, Caroline (Cranfield University, 2015)
This year we have seen significant progress on FTSE 100 boards. All-male boards have totally disappeared with Glencore, the last, appointing a woman to its board. The percentage of women on FTSE 100 boards is 23.5%, almost exactly where we predicted in last year's report. This puts us on track to hit the 25% target by the end of 2015. The percentage of women in executive directorships on FTSE 100 boards is at an all time high of 8.6% with 24 women holding such roles.